Motivational Aspect of Good Governance (The Pakistan Development Review, 1999)
A government job is what most job seekers look for in Pakistan. With a feudal background and job culture inherited from British India, government jobs are believed to provide security, permanency, status and privileged treatment in day to day affairs. But where entering into government jobs is attractive, working in a government atmosphere is often found to be boring, monotonous, and devoid of enthusiasm. Attending office is a matter of killing time. One comes late and leaves early. There is no incentive to work hard, as promotions and benefits depend on seniority not on performance. Coercion seems to be the only management technique, which at times fails or fires back if the manager is not very tactful. Management theories and motivational concepts are foreign names in government departments. Without including the motivational aspects of good governance it would be futile to try to improve performance.